Eradicating Extreme Poverty in Bengkalis Regency: A Strategic Breakthrough with Holistic Approach - Asrofillah, Muhammad Fuad; Arimurti, Rizqa; Rambe, Armita Novriana (Journal of Public Representative and Society Provision, 2024)
Extreme poverty in Bengkalis Regency is one of the main challenges of regional development, especially in coastal and island areas. This article analyzes strategies to accelerate the elimination of extreme poverty by using a holistic approach of socio-economic programs and government intervention innovations. The study focuses on programs such as Gerakan Desa Mandiri and Direct Cash Assistance that are designed to improve the welfare of extreme poor households through entrepreneurship training, cash transfers, and basic infrastructure development. Using data from the 2023 Integrated Database Updating (PBDT) and 2024 BPS, multiple linear regression analysis was conducted to identify the determinants of program success. Results show an extreme poverty reduction of 7% between 2023 and 2024, with the highest achievements in Mandau (31%) and Rupat (23%) sub-districts. However, major challenges remain in remote areas such as Bengkalis sub-district. This article suggests intensification of community-based programs, improving access to employment, and cross-sector coordination to achieve the target of eliminating extreme poverty by 2025.